The Energy–Matter–Behavioral Model of Mental Health Hygiene: A Systems-Based Framework for Sustainable Well-Being - Mark Clark (Journal of Behavior Therapy And Mental Health, 2025)
The Energy–Matter–Behavioral (EMB) model offers a systems-based lens for understanding and maintaining mental health hygiene. This framework integrates stress reduction, biological resilience, and behavioral reinforcement into a coherent triad, addressing not only symptoms but underlying energetic and material dynamics. By aligning practices such as exercise, meditation, social connection, sleep, and diet with EMB principles, this model presents a transdisciplinary, evidence-informed approach to mental health in an overstimulated world.
Keywords: Mental health hygiene